Politeness Strategies in Mark and Eric Nam’s Podcast on Dive Studios YouTube Channel: A Pragmatic Analysis - Nurmalia, Lia Nurmalia; Fazharani, Rahma (LPPM Universitas Bina Sarana Informatika, 2025)
The objectives of this research are to analyze the use of positive politeness strategies and the number of positive politeness strategies found in Mark and Eric Nam's podcast using the theory of Brown and Levinson. This research is designed using a qualitative descriptive method, which involves explaining the utterances and purpose of the conversation in Mark and Eric Nam's podcast, related to positive politeness strategies. Research data was obtained from the episode of